PELAKSANAAN PENGAWASAN KERJA KARYAWAN (Kasus Pada Karyawan Kebun PT. Perkebunan Nusantara V Unit Terantam) - Abdi Ramagiri; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
One of the companies belonging to BUMN engaged in the palm oil industry is PT. Plantation terantam V Riau, which is located in subdistrict Tapubg Hulu, district Kampar. It is a company that is doing the processing of fresh fruit bunches (FEB) that is derived from their own gardens. PT. Plantation Terantam V Riau also been known to have a good image because always able to achieve the target set by the company. However, in the last few years, the company get a drop in achieving the target.The purpose of this research was to investigate the implementation of surveillance conducted by the leader in the company. Which after meticulous, it turn out the implementation of the existing surveillance on the archipelago PT. Plantation Terantam V Riau which has been classified in a accordance with a score of 2361 which is in the range 1828-2390. Therefore the leaders in the company should pay more attention and more about implementation of supervision so that the results can be realized with good companyKeyword: Work Supervision, Leadership, Labours